2021
DOI: 10.1007/s12687-020-00498-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of insurance on equitable access to non-invasive prenatal screening (NIPT): private insurance may not pay

Abstract: Non-invasive prenatal testing (NIPT), is a prenatal screening test for chromosomal aneuploidies (trisomy 21, trisomy 18, and trisomy 13). While women under 35 years of age with no other risk factors are considered low risk for pregnancies with aneuploidy, most babies with aneuploidy are born to low-risk women. Across the USA, including Wisconsin, many private insurances do not cover initial NIPT for low-risk women, creating a potential financial burden that may limit patient selection of NIPT. Low-risk women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…This supports concerns regarding potential disparities in the uptake of NIPT, which conflicts with the primary goals of a government‐supported national screening program of equitable access and reproductive autonomy. Our study corroborates findings from other high‐income countries such as Australia, 17,18 the United Kingdom 12 and the United States, 19 where socioeconomic disparities in fetal aneuploidy screening uptake were also reported.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This supports concerns regarding potential disparities in the uptake of NIPT, which conflicts with the primary goals of a government‐supported national screening program of equitable access and reproductive autonomy. Our study corroborates findings from other high‐income countries such as Australia, 17,18 the United Kingdom 12 and the United States, 19 where socioeconomic disparities in fetal aneuploidy screening uptake were also reported.…”
Section: Discussionsupporting
confidence: 90%
“…On the one hand, it has been argued that a (small) financial barrier may encourage informed decision‐making among pregnant women by promoting deliberation 20 . On the other hand, requiring a payment for NIPT could actively hinder equitable access to the test due to women being unable to pay for fetal aneuploidy screening, thus impeding on their freedom to choose 5,19 . A survey study among European healthcare providers indicated that the costs and a lack of reimbursement policy were considered to be the primary barrier to broader NIPT uptake 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 14 Moreover, the cost of NIPT varies widely, which creates a potential financial burden for pregnant women in low-income and middle-income countries. 15 These factors may further limit the widespread use of NIPT. 16 In China, the price of NIPT in the private sectors varies from US$202.49 to US$332.46, as the cost is only partially covered by health insurance in most provinces, pregnant women may have to bear the cost for this service.…”
Section: Open Accessmentioning
confidence: 99%
“…However, the high overall costs and operational complexities of the NGS-NIPT might hinder its implementation to a wide-spread clinical routine practice. Even though, the NGS-NIPT has been recommended in many counties as the first-tier screen method for fetal aneuploidies screen, majority of pregnant women cannot afford to choose this test because it is currently not universally covered by healthcare systems or private insurances [ 30 , 31 ]. To effectively balance the benefits and higher cost regarding the NGS-NIPT, many countries select the contingent strategy (CS) that uses the SBT as a primary screen tool and use the NGS-NIPT as a confirmation test for the high risk pregnancies identified by the SBT.…”
Section: Introductionmentioning
confidence: 99%